Bantuan sosial Sebagai Instrumen Politik Uang Non-Tunai dalam Pemilu Indonesia - Angreinni Angreinni; Muhammad Junaidi; Kukuh Sudarmanto; Albertus Heru Nuswanto; Suryani Angraini Fahmi (JURNAL USM LAW REVIEW, 2026)
The purpose of this study is to analyze the potential transformation of social assistance (Bansos) into a non-cash vote-buying instrument in Indonesian elections and to identify regulatory and governance weaknesses that facilitate such practices. This research employs a juridical-normative approach supported by conceptual analysis and literature review of electoral laws and social assistance policies. The findings reveal a regulatory gap in the Election Law that fails to explicitly accommodate policy-based non-cash vote buying, alongside legal ambiguity in distinguishing legitimate public policy from electoral instruments, and governance failure reflected in weak transparency, accountability, and bureaucratic neutrality in Bansos distribution. Concrete indicators of politicization include pre-election distribution surges (electoral timing), program personalization, and biased beneficiary selection. The novelty of this study lies in formulating the concept of policy-based non-cash vote buying as an expansion of vote-buying categorization within electoral law, complemented by a typology of politicization mechanisms and monitoring indicators. This study contributes to advancing electoral law reform through an effect-based approach, strengthening institutional oversight, and improving transparent and accountable Bansos governance to uphold electoral integrity and fairness. Tujuan penelitian ini adalah menganalisis potensi transformasi bantuan sosial (Bansos) sebagai instrumen politik uang non-tunai dalam Pemilu Indonesia serta mengidentifikasi kelemahan regulasi dan tata kelola yang memfasilitasinya. Penelitian ini menggunakan pendekatan yuridis-normatif dengan dukungan analisis konseptual dan studi literatur terhadap regulasi Pemilu dan kebijakan bansos. Hasil penelitian menunjukkan adanya regulatory gap dalam Undang-Undang Pemilu yang belum mengakomodasi politik uang non-tunai berbasis kebijakan publik, disertai legal ambiguity dalam batas antara kebijakan sosial dan instrumen elektoral, serta governance failure yang tercermin dari lemahnya transparansi, akuntabilitas, dan netralitas birokrasi dalam distribusi Bansos. Indikator konkret politisasi Bansos meliputi peningkatan distribusi menjelang Pemilu (electoral timing), personalisasi program, dan bias dalam penentuan penerima. Kebaruan penelitian ini terletak pada pengembangan konsep policy-based non-cash vote buying sebagai perluasan kategorisasi politik uang dalam hukum Pemilu, disertai tipologi mekanisme politisasi Bansos dan indikator pengawasannya. Kontribusi penelitian ini mendorong reformulasi hukum Pemilu berbasis pendekatan dampak, penguatan pengawasan kelembagaan, serta perbaikan tata kelola Bansos yang transparan dan akuntabel guna menjaga integritas dan keadilan elektoral.